THE USE OF CTL TO IMPROVE THE SPEAKING SKILL ON ENGLISH FOR TOURISM IN THE FIRST SEMESTER OF THE TOURISM STUDY PROGRAM OF UNIVERSITAS HAMZANWADI - Ramli, Muhammad; Supriadi, Herman; Apriyeni, Baiq Ahda Razula (Institut Agama Islam Negeri (IAIN) Bone, 2025)
English has been taught since elementary school up to the university. The students are taught of language's skills, but most of the students still hard to use English as spoken language especially for students at a former place. This classroom action research implemented the CTL approach to improve the teaching and learning and students' speaking skill in form of transactional and interpersonal speech. The main object of this research is the students of tourism study program of Hamzanwadi University. It was conducted in three cycles, the overview of those cycles can be seen from the following results; 1) the contextual teaching and learning could improve the lecturing process, 2) the students' participation to practice speaking was improved cycle by cycle; 49% was in cycle 1, then improved to 71.44% and 91.4% in cycle II and cycle III, and 3) the students' speaking improvement was also shown from the mean score and the category of students' speaking ability. The mean score in pre-cycle was 33 and then improved to be 41 in cycle I, 52 in cycle II and 75 in cycle III. The category of students' speaking ability fell in very good, good and fairly good categories.